2010
DOI: 10.1016/j.neulet.2010.03.060
|View full text |Cite
|
Sign up to set email alerts
|

High frequency stimulation of the subthalamic nucleus evokes striatal dopamine release in a large animal model of human DBS neurosurgery

Abstract: Subthalamic nucleus deep brain stimulation (STN DBS) ameliorates motor symptoms of Parkinson’s disease, but the precise mechanism is still unknown. Here, using a large animal (pig) model of human STN DBS neurosurgery, we utilized fast-scan cyclic voltammetry in combination with a carbon-fiber microelectrode (CFM) implanted into the striatum to monitor dopamine release evoked by electrical stimulation at a human DBS electrode (Medtronic 3389) that was stereotactically implanted into the STN using MRI and electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
84
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 105 publications
(88 citation statements)
references
References 30 publications
4
84
0
Order By: Relevance
“…Although exactly how DBS modulates STN LF activity remains open to conjecture, electrical polarization around the DBS electrode could modulate activity in STN neurons and, given that we recorded similar STN LF power in patients on medication and on DBS, suggests that polarization could act similarly to levodopa. Some studies have highlighted the striatal dopamine release during high-frequency DBS [41,42,43,44]. Hence, again given the similar STN LF power changes recorded on medication and during DBS, the DBS-induced striatal dopamine release and levodopa medication could correspond to the LF power increase in a similar manner [18,24].…”
Section: Discussionmentioning
confidence: 98%
“…Although exactly how DBS modulates STN LF activity remains open to conjecture, electrical polarization around the DBS electrode could modulate activity in STN neurons and, given that we recorded similar STN LF power in patients on medication and on DBS, suggests that polarization could act similarly to levodopa. Some studies have highlighted the striatal dopamine release during high-frequency DBS [41,42,43,44]. Hence, again given the similar STN LF power changes recorded on medication and during DBS, the DBS-induced striatal dopamine release and levodopa medication could correspond to the LF power increase in a similar manner [18,24].…”
Section: Discussionmentioning
confidence: 98%
“…The immediate positive effects on psychiatric symptoms, such as depression, anxiety and fatigue, might be mediated through direct involvement of STN in fear-processing networks and limbic circuits, as well as indirect dopaminergic effects of STN-DBS [20,26,27]. The occurrence of anxiety and acute worsening of depression were most likely due to misplacing of electrodes ventrally to the STN [28], while optimal electrode positions can lead to immediate anti-depressive and mood-elevating effects [29].…”
Section: Discussionmentioning
confidence: 99%
“…37 We have previously reported that high-frequency stimulation of the subthalamic nucleus increases glutamate and dopamine levels in rats and large animal models. 38,39 Thus, it is not unreasonable to presume that high-frequency stimulation of the NAC may also result in glutamate and dopamine release, which could result in analgesia through unknown downstream effects.…”
Section: Discussionmentioning
confidence: 99%